Mining Claim Disputes in Ontario - Lauwers, Peter (Revue générale de droit, 1986)
1. General. Mining claim disputes in Ontario usually arise where a restaker attempts to dispute the validity of a claim under the provisions of the Mining Act.2. Staking and Recording Requirements. Most mining claim disputes turn on whether there has been substantial compliance with the statutory staking requirements. A number of rules of thumb have evolved to assist the Mining Commissioner in making his decision as to whether there has been substantial compliance. These include the purpose test, the cumulative errors test, the reasonable excuse test, the equitable approach, the application of different staking standards and different circumstances, and classification of the seriousness of errors. The text also contains a discussion of the statutory staking and recording requirements.3. Procedural Requirements in Disputes and Appeals. Staking disputes are ordinarily heard at first instance by the Mining Recorder, and then by the Mining Commissioner on appeal. The decisions of the Mining Commissioner may be appealed to the Divisional Court, a branch of the Supreme Court of Ontario. Specific emphasis is placed on the strictness of the time limits under the statute.